Tunable Low Loss 1D Surface Plasmons in InAs Nanowires. Issue 35 (10th July 2018) - Zhou, Yixi; Chen, Runkun; Wang, Jingyun; Huang, Yisheng; Li, Ming; Xing, Yingjie; Duan, Jiahua; Chen, Jianjun; Farrell, James D.; Xu, H. Q.; Chen, Jianing
Abstract: Due to the ability to manipulate photons at nanoscale, plasmonics has become one of the most important branches in nanophotonics. The prerequisites for the technological application of plasmons include high confining ability (λ0 /λp ), low damping, and easy tunability. However, plasmons in typical plasmonic materials, i.e., noble metals, cannot satisfy these three requirements simultaneously and cause a disconnection to modern electronics. Here, the indium arsenide (InAs) nanowire is identified as a material that satisfies all the three prerequisites, providing a natural analogy with modern electronics. The dispersion relation of InAs plasmons is determined using the nanoinfrared imaging technique, and show that their associated wavelengths and damping ratio can be tuned by altering the nanowire diameter and dielectric environment. The InAs plasmons possess advantages such as high confining ability, low loss, and ease of fabrication. The observation of InAs plasmons could enable novel plasmonic circuits for future subwavelength applications. Abstract : Indium arsenide (InAs) nanowires fabricated by chemical vapor deposition method are demonstrated to be a tunable plasmonic material. 1D InAs plasmons are first observed in real space and simultaneously exhibit high spatial confinement and low loss damping. By changing the substrate and varying nanowire size, the physical properties of InAs plasmons can be effectively controlled.